A Model for the Prediction of the Redox Potentials in [FeFe]‐Clusters from the Electronic Properties of Isocyanide Ligands. Issue 24 (24th June 2020) - Collado, Alba; Torres, Alejandro; Gómez‐Gallego, Mar; Casarrubios, Luis; Sierra, Miguel A.
Abstract: Using an experimental‐computational methodology, arylisocyanides (CNAr) have shown to be excellent probes to study the effect of electronic properties in the electrochemical behavior of [FeFe]‐complexes. The calculated LUMO distribution of p‐ substituted [Fe2 {(μ‐SCH2 )2 N t Bu}(CO)5 (CNAr)] complexes (2 ) show that, depending on the substituent, the first reduction event ( Epc ) may be metal centered or ligand centered. The electrochemical response of complexes 2 has been experimentally studied and correlated to the calculations performed. The Epc values were found to directly correlate to different spectroscopic properties such as IR and 13 C{ 1 H} NMR spectroscopies. These findings could be used to predict the Epc values of new [FeFe]‐complexes. Abstract : The effect of the electronic properties of isocyanide ligands in the electrochemical behavior of [Fe2 {(μ‐SCH2 )2 N t Bu}(CO)5 (CNAr)] complexes has been studied and could be used to predict the Epc values of new [FeFe]‐species.